Correlation of Thorax Expansion with Heart Rate and Blood Pressure in School-Aged Children - Pipit Wandini; Ellyana Sungkar; M. Rizki Akbar (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Background: Thorax expansion used to measure respiratory function. Data of thorax expansion for healthychildren is still limited. Thorax expansion is caused by breathing. This influences cardiovascular functionbecause anatomically the heart is located within the thorax cavity. The aim of this study is to determine themeasurement of thorax expansion using the measurement tape method. Factors influencing thorax expansionare sex and age; and correlates with heart rate and blood pressure in school age children.Methods: Ninety-six children were included in this study both male and female and were aged 6 to 15years. They were in Elementary School and Junior High School in Jatinangor. The study were conductedfrom September-November 2013 by adopting a random selection cross sectional method. The examinationsperformed after written informed consent and questionnaire form from their parents.Results: The results showed that upper thorax has lower mean expansion than middle and lower thoraxexpansion respectively (2.96±0.64cm; 3.82±1.04cm; 5.01±1.15cm). There was significant difference betweengroups of age (p<0.05). This study also found that there was a correlation between the upper and middle thoraxexpansion with the heart rate (r=0.35; p=0.001, and r=0.32; p=0.002).Conclusions: The mean of thorax expansion at upper, middle and lower respectively (2.96±0.64cm;3.82±1.04cm; 5.01±1.15cm) are influenced by age and has correlation with heart rate.Keywords: blood pressure, heart rate, school-aged children, thorax expansion.